2021
DOI: 10.3390/ijms23010062
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein CIII Reduction Protects White Adipose Tissues against Obesity-Induced Inflammation and Insulin Resistance in Mice

Abstract: Apolipoprotein CIII (apoCIII) is proinflammatory and increases in high-fat diet (HFD)-induced obesity and insulin resistance. We have previously shown that reducing apoCIII improves insulin sensitivity in vivo by complex mechanisms involving liver and brown adipose tissue. In this study the focus was on subcutaneous (SAT) and visceral (VAT) white adipose tissue (WAT). Mice were either given HFD for 14 weeks and directly from start also treated with antisense oligonucleotide (ASO) against apoCIII or given HFD f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The proinflammatory agent Apolipoprotein C-III ( Apoc3 ), down-regulated in white adipose tissue and the kidney, is associated with T2D, heart, and kidney diseases. Apoc3 reduction in mice was recently demonstrated to protect white adipose tissues against obesity-induced inflammation and insulin resistance 72 . Overall, these results support a high concordance of our rat-based data with human studies and their relevance to human disease.…”
Section: Resultsmentioning
confidence: 99%
“…The proinflammatory agent Apolipoprotein C-III ( Apoc3 ), down-regulated in white adipose tissue and the kidney, is associated with T2D, heart, and kidney diseases. Apoc3 reduction in mice was recently demonstrated to protect white adipose tissues against obesity-induced inflammation and insulin resistance 72 . Overall, these results support a high concordance of our rat-based data with human studies and their relevance to human disease.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, decreasing ApoC-III ameliorates insulin sensitivity and triglyceride levels [65]. In a very recent study focused on subcutaneous (SAT) and visceral (VAT) white adipose tissue (WAT), Recio-Lopez et al have found that lowering ApoC-III determines improvements of metabolic status, decreases inflammation and size of adipocytes in WAT, and enhances the expression of genes related to thermogenesis and functions of SAT [66].…”
Section: Apoc-iii: Obesity and Lipodystrophymentioning
confidence: 99%